2018
DOI: 10.1002/ldr.3223
|View full text |Cite
|
Sign up to set email alerts
|

Decline in soil moisture due to vegetation restoration on the Loess Plateau of China

Abstract: Afforestation brings lots of water‐related benefits, including reducing soil erosion and improving water conservation, simultaneously; it is considered to be a land use activity, which threatens water resources security. Characterizing the response of soil moisture to revegetation is important for the sustainability of water and plants on the Loess Plateau of China. In this study, we conducted a meta‐analysis of 1,262 observations from 66 published studies to evaluate the effect of land use on the soil moistur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(52 citation statements)
references
References 40 publications
3
48
1
Order By: Relevance
“…Compared with deciduous trees, the evergreen trees can allocate more photosynthetic products for fine root production (Vogt et al , 1986) which was supported by Gao and Huang (2020). In terms of soil water depletion, Su and Shangguan (2019) reported that there were no significant differences between deciduous and evergreen tree species in the Loess Plateau at a regional scale which was consistent with our results (Fig.6). Overall, the vegetation types or tree species exhibited great impacts on the trade-off between soil water maintenance and carbon sequestration, and grassland has the potential to achieve this win-win situation.…”
Section: Land-use Conversion Typessupporting
confidence: 90%
See 1 more Smart Citation
“…Compared with deciduous trees, the evergreen trees can allocate more photosynthetic products for fine root production (Vogt et al , 1986) which was supported by Gao and Huang (2020). In terms of soil water depletion, Su and Shangguan (2019) reported that there were no significant differences between deciduous and evergreen tree species in the Loess Plateau at a regional scale which was consistent with our results (Fig.6). Overall, the vegetation types or tree species exhibited great impacts on the trade-off between soil water maintenance and carbon sequestration, and grassland has the potential to achieve this win-win situation.…”
Section: Land-use Conversion Typessupporting
confidence: 90%
“…As is typical in meta-analysis, most of the published papers reported mean values for treatment and control plots but not standard deviations or standard errors. To maximize the number of observations included in the present analysis, we used unweighted meta-analysis, as described in earlier studies (Deng et al , 2016;Su and Shangguan, 2019).…”
Section: Meta-analysismentioning
confidence: 99%
“…Recently, many studies have pointed that conversions of land use types and vegetation recovery led to the decline of local soil water storage. Particularly in regions with a remarkable vegetation increase or large area of artificially planted exotic species, overconsumption of soil water resulted in a widespread dry soil layer [57,72]. Observations showed that the soil water contents under Robinia pseudoacacia, one of the main afforestation species in the Loess Plateau, decreased rapidly [73] and the drying layer extended from shallow layers (0-100 cm) to deeper layers (100-500 cm) with increasing forest age [74].…”
Section: Implications Of Vegetation Change Sustainability In Ecologicmentioning
confidence: 99%
“…And the relationships between rainfall and surface runoff in these places are relatively stronger (Figure 5). However, although the forest cover area significantly increased for the Beiluo River basin in P2, the runoff coefficient still remained small (<0.1), which may also correlate with increased consumption of water due to the growth of secondary vegetation (Su & Shangguan, 2019).…”
Section: Discussionmentioning
confidence: 99%